Alkali influence on ZnO and Ag-doped ZnO nanostructures formation using the microwave-assisted hydrothermal method for fungicidal inhibition. (November 2021) - Gusmão, Luiza A.; Peixoto, Diego A.; Marinho, Juliane Z.; Romeiro, Fernanda C.; Gonçalves, Rosana F.; Longo, Elson; de Oliveira, Carlos A.; Lima, Renata C.
Abstract: This study reports on the effect of the alkali source in pure ZnO and Ag-doped ZnO samples formation quickly synthesized using the microwave-assisted hydrothermal (MAH) method. The flower-like morphology of ZnO and Ag-doped ZnO samples was controlled by the presence of ammonia under reaction conditions, which provided slower ZnO nucleation. In the presence of sodium hydroxide, the precursor species were instantaneously formed, promoting a rapid ZnO formation and the obtainment of Ag 0 in the Ag-doped ZnO sample. The presence of Ag + ions into ZnO wurtzite structure created defects, contributing to a local structural disorder, as observed by Raman spectra. All the samples studied herein presented antifungal activity for Saccharomyces cerevisiae, which was influenced because of the presence of Ag + ions into ZnO lattice and the morphologies of the samples. Graphical abstract: Nucleation processes from different alkali sources contribute to morphologies and properties of ZnO samples and Ag-doped ZnO. Image 1 Highlights: Rapid synthesis of ZnO and Ag–ZnO were obtained via heating microwave-hydrothermal. Using ammonia leads to effective Ag-doping and results in flower-like structures. Using NaOH results in Ag phase formation and irregular morphology. A defined morphology of pure ZnO sample promote a greater S. cerevisiae inhibition. Ag generates extra Ag + and free electrons responsible for the fungicidal inhibition.